The social dimensions of Philippine English - Gonzalez, Andrew B. (Animo Repository, 2004)
The context of Philippine English is described in terms of its historical, social, political and economic dimensions. The past is reviewed to explain the present, and the contemporary status and characteristics of this Philippine variety are outlined. Some tentative predictions are made as to its future, based on current social and economic trends in the area. A statement is attempted on the factors contributing to the maintenance of a standardized Asian variety of English (mutually intelligible with other world varieties) as well as factors contributing to the rise of Englishes which will eventually be mutually unintelligible (in the same way that Latin devolved to the Romance languages as the Roman Empire gave rise to independent nation-states). © 2004 Wiley. All rights reserved.